Fourty years of the Revista del Jardín Botánico Nacional: a bibliometric analysis - Báez, Estrellita Fornés; Puerta-Díaz, Mirelys [UNESP]; Falcón-Hidalgo, Banessa; Marti-Lahera, Yohannis (My University, 2021)
In 2020, the Revista del Jardín Botánico Nacional celebrated its 40th anniversary. This study aims to stage an updated analysis of its publications to provide a general overview of the journal, focusing on a bibliometric analysis of its publications between 1980 and 2020. The methodology involves two procedures: 1) performance analysis to characterize the evolution of its productivity, visibility, and impact and 2) social network analysis for analysis of author co-occurrence maps. Also, some alternative indicators related to usage are considered in journal performance analysis of the last three years. The co-authorship structure exposed that the most productive and most cited authors were those who had more publications in co-authorship, with a greater diversity of co-authors and co-published with at least one author from a group other than their own. Main findings indicate that the Journal of National Botanic Garden has published transcendental works contributing to the construction of new scientific knowledge since its inception, and its quality as a scientific journal has been consolidated over time.
Cuarenta años de la Revista del Jardín Botánico Nacional: un análisis bibliométrico
Keywords: altmetrics; bibliometrics; journal analysis; National Botanic Garden; scientific journal